THE EFFECT OF PAPAYA FRUIT (CARICA PAPAYA) TOWARD BREAST MILK PRODUCTION ON POSTPARTUM MOTHERS - Tri Utami, Iis; Komala Sari, Vitria; Wahyuni, Wahyuni; Agustina, Rika (Universitas Aisyah Pringsewu, 2023)
A recurring issue encountered by postpartum mothers in breastfeeding is the occurrence of insufficient milk production (32%). Papaya fruit contains substances like Lactogogum, Vitamin A, and Vitamin C, which are known to enhance milk production. This study aimed to investigate the impact of papaya fruit (Carica papaya) on milk production in postpartum mothers within the operational realm of the Talu Public Health Center in 2023. Employing a quantitative research approach, the study utilized a quasi-experimental design featuring a one-group pretest-posttest setup.The study encompassed the entire population of postpartum mothers in Talu Community Health Center's jurisdiction, totaling 225 individuals. A sample of 30 participants was selected using a purposive sampling technique. Data analysis involved both univariate and bivariate methods, employing the Wilcoxon test. Statistical findings demonstrated that the average breast milk production score prior to the intervention (papaya fruit) was 4.27. Following the intervention (papaya fruit consumption), the average breast milk production score increased to 4.80. The bivariate test yielded a p-value of 0.000, indicating a significant impact of the intervention on breast milk production. In conclusion, it is established that giving papaya fruit has a positive effect on breast milk production among postpartum mothers within Talu Community Health Center's jurisdiction in 2023. The study suggests that regular consumption of fruits rich in Lactogogum, Vitamin A, and Vitamin C, such as papaya, can potentially enhance milk production for postpartum mothers.